Regulatory environment of fintech on the example of PSD2 directive and chosen internal laws - Gawron , Oliwia (Journal of Finance and Financial Law, 2019)
Nowadays in digital age many financial institutions decide to cooperate with FinTech entities. Such decision allows them to create brand new products and improve those in their pipeline. However financial market is not always ready for such innovations. With scarce and vague regulations, FinTech sector is not always able to guarantee the safety of consumers’ fundsand FinTech entities may in the worst case scenario not be allowed to function on financial market. Therefore all actions leading to stable regulations are deemed especially important.The aim of this article is to present the chosen regulations of this sector and assess whether they are sufficient.